2006
DOI: 10.1007/bf03033929
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of non-a botulinum toxins: botulinum toxin type B

Abstract: Botulinum neurotoxin type B (BT, BT-B) has been used as NeuroBloc/MyoBloc since 1999 for treatment of cervical dystonia, hyperhidrosis, spastic conditions, cerebral palsy, hemifacial spasm, bladder dysfunction, spasmodic dysphonia, sialorrhoea, anal fissures, piriformis syndrome, various pain conditions and cosmetic applications. Generally, its therapeutic effects are comparable to BT type A (BT-A). The adverse effect profiles of BT-B and BT-A, however, differ considerably. BT-B has been found to produce more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…This may be of importance since the frequency of de novo BTX-B immuno-resistant cases is high (which may in part be due to the higher protein content), and associated with a poorer clinical response, at least in patients treated for cervical dystonia [28,29]. However, it should be considered that the mean doses used for treating sialorrhea are smaller than those used for cervical dystonia, the mean treatment duration is longer than for cervical dystonia, and that the survival of ALS patients with severe bulbar symptoms is short.…”
Section: Discussionmentioning
confidence: 99%
“…This may be of importance since the frequency of de novo BTX-B immuno-resistant cases is high (which may in part be due to the higher protein content), and associated with a poorer clinical response, at least in patients treated for cervical dystonia [28,29]. However, it should be considered that the mean doses used for treating sialorrhea are smaller than those used for cervical dystonia, the mean treatment duration is longer than for cervical dystonia, and that the survival of ALS patients with severe bulbar symptoms is short.…”
Section: Discussionmentioning
confidence: 99%
“…This is suggested not only by the study included in the present review, 28 but also by trials with BoNT/B for other indications. 45 Six studies reported inconsistent and conflicting results on pain reduction in the upper limb following BoNT treatment, 10,11,21,25,26,28 whereas one controlled study showed significant pain reduction in the lower limb. 27 These inconsistencies in secondary outcome measures are likely explained by the heterogeneity of patients included and by the lack of systematic evaluation of pain or disability as outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…7,16 BT type B has been used since 1999 for the treatment of cervical dystonia, hyperhidrosis, spastic conditions, cerebral palsy, hemifacial spasm, bladder dysfunction, and various pain conditions. 17 Compared with type A, type B is thought to have a greater affinity for the sympathetic nerve system and therefore is more likely to relieve pain than the type A toxin. 17 A dosage of 5000 U of type B injection in patients with piriformis syndrome significantly reduced buttock and lower limb pain and these pain relieving effects were maintained at 16 weeks after injection.…”
mentioning
confidence: 99%